2005
DOI: 10.1037/0022-006x.73.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Sudden Gains in Acute Phase Treatment of Depression.

Abstract: The authors examined the validity of sudden gains identified with T. Z. Tang and R. J. DeRubeis's (1999) method in 2 clinical data sets that involved treatment of major depressive disorder (N=227). Sudden gains replicated among self- and clinician reports of depressive symptoms and predicted better psychosocial functioning at the acute phase treatment end point, in support of their validity. However, sudden gains occurred with roughly the same moderate frequency in pill placebo and pharmacotherapy with clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
167
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(194 citation statements)
references
References 46 publications
(108 reference statements)
23
167
3
1
Order By: Relevance
“…In contrast, we observed no differences in outcome between individuals with and without sudden gains at the posttreatment or 6-month follow-up assessments. This finding is in line with some studies (Tang et al, 2002;Vittengl et al, 2005) but at odds with other reports (Gaynor et al, 2003;Hardy et al, 2005).It is interesting that we found that participants with sudden gains had higher levels of pretreatment social anxiety. Similarly, previous studies on sudden gains during the treatment for depression also observed higher levels of pretreatment symptomatology in individuals who later experienced sudden gains (e.g., Vittengl et al, 2005).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, we observed no differences in outcome between individuals with and without sudden gains at the posttreatment or 6-month follow-up assessments. This finding is in line with some studies (Tang et al, 2002;Vittengl et al, 2005) but at odds with other reports (Gaynor et al, 2003;Hardy et al, 2005).It is interesting that we found that participants with sudden gains had higher levels of pretreatment social anxiety. Similarly, previous studies on sudden gains during the treatment for depression also observed higher levels of pretreatment symptomatology in individuals who later experienced sudden gains (e.g., Vittengl et al, 2005).…”
supporting
confidence: 91%
“…Sudden gains are typically defined by a set of three quantitative criteria: (a) the sudden gain must be large in absolute terms, (b) the sudden gain must represent at least a 25% reduction from the level of symptomatology before the gain occurred, and (c) the mean level of symptomatology in the three therapy sessions preceding the gain must be significantly higher than the mean level of symptomatology in the three postgain sessions. Most studies of sudden gains have examined treatment changes in depression with the Beck Depression Inventory (BDI; Beck, Ward, Mendelson, Mock, & Erbaugh, 1961; but see also Stiles et al, 2003;Vittengl, Clark, & Jarrett, 2005).When applying these criteria, Tang and DeRubeis (1999b) found that sudden gains occurred in more than 50% of individuals who responded to cognitive-behavioral therapy for depression and that these gains accounted for more than 50% of these individuals' total improvement in depression. Compared with participants who did not experience sudden gains at posttreatment, individuals with sudden gains showed better outcome at posttreatment and at 6-month and 18-month follow-ups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although plots of averaged symptom change at pre-, mid-, and post-treatment suggested gradual and linear change, Tang and colleagues (Tang & DeRubeis, 1999;Tang, DeRubeis, & Beberman, & Pham, 2005) found that plots of individual time course data revealed that about 39% to 46% of patients experienced a sudden gain and that this nonlinear pattern predicted improvement in depression. Sudden gains also have been associated with better functioning in at the end of treatment in supportive-expressive therapy (Tang, Luborsky, & Andrusyna, 2002), nonmanualized psychotherapies in routine clinical practices (Stiles et al, 2003), systematic behavioral family therapy (Gaynor et al, 2003), and CBT for recurrent and atypical depression (Vittengl, Clark, & Jarrett, 2005).…”
Section: Depressionmentioning
confidence: 99%
“…To date, these "sudden gains" have been identified as occurring during the active phase of treatment in a variety of psychotherapies for depression, including cognitive therapy (Tang & DeRubeis, 1999b;Tang et al 2005), brief psychodynamic therapy (Tang, Luborsky & Andrusnya 2002;Andrusnya, Luborsky, Pham & Tang, 2006), and group psychoeducational treatment (Kelly, Roberts & Ciesla, 2005). Sudden gains also occur in mental health clinic "treatment as usual" (Stiles et al, 2003), among placebo control groups (Vittengl et al, 2005) and among non-treated samples (Kelly, Roberts & Bottonari, 2007). Further, there is some evidence that individuals who experience sudden gains have better acute treatment outcomes and do better in long-term follow-up than those whose symptom improvement is more gradual (Tang & DeRubeis, 1999b;Tang, Luborsky & Andrusnya 2002;Tang, DeRubeis, Hollon, Amsterdam & Shelton, 2007; see also Grilo, Masheb, & Wilson, 2006, for related results in binge-eating disorder).…”
Section: Introductionmentioning
confidence: 99%